2017
DOI: 10.1371/journal.pone.0177704
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic cycling—What do we know? A scoping review on head-out aquatic cycling

Abstract: Over the past few years, aquatic cycling has become a trending fitness activity. However, the literature has not been reviewed exhaustively. Therefore, using scoping review methodology, the aim of this review was to explore the current state of the literature concerning aquatic cycling. This study specifically focused on study designs, populations and outcomes. A comprehensive search of seven databases (PubMed, MEDLINE, Cinahl, Embase, PEDro,Web of Science, WorldCat) was conducted up to 30th September 2016. Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Therefore, water-based exercises are suitable for special groups such as postmenopausal women and older adults 21 . Several previous studies showed that aquatic exercise training had cardiovascular benefits 22,23 , especially for those with high risk musculoskeletal conditions 24 .…”
mentioning
confidence: 99%
“…Therefore, water-based exercises are suitable for special groups such as postmenopausal women and older adults 21 . Several previous studies showed that aquatic exercise training had cardiovascular benefits 22,23 , especially for those with high risk musculoskeletal conditions 24 .…”
mentioning
confidence: 99%
“…Os parâmetros cardiovasculares foram investigados por muitos dos estudos envolvendo ciclismo aquático e os resultados sugerem que a exigência cardíaca de ciclismo aquático parece ser semelhante ao ciclismo terrestre (13) .…”
Section: Desenvolvimentounclassified
“…The popularity of water-based activities, mainly aqua-cycling, has shown an impressive progression for the last couple of years, especially in women who are looking for weight control and weight management. A recent systematic review from Rewald et al [ 3 ] showed that studies comparing land- vs. water-based exercises mainly focused on cardiovascular adaptations during protocols for maximal aerobic capacity testing. Brechat et al [ 4 ] have studied the metabolic adaptations to water-cycling exercise in healthy young men, showing a 25% increased oxygen consumption during water compared with land exercise.…”
Section: Introductionmentioning
confidence: 99%